Switching of supramolecular nanostructures at the solid-liquid interface: interplay of bias polarity and solution concentration - Jia, Baoxin; Enache, Mihaela; Gliemann, Bettina D.; Jocic, Angelina; Kivala, Milan; Stöhr, Meike (Nanoscale advances, 2025)
The self-assembly of a carboxy-functionalized triarylamine derivative (CTA) at the nonanoic acid-highly oriented pyrolytic graphite (NA-HOPG) interface is investigated using scanning tunnelling microscopy (STM). The study reveals that CTA molecules can self-assemble into diverse two-dimensional long-range ordered networks at the NA-HOPG interface, with their formation influenced by the concentration of the solution and the bias voltage of the STM tip. Moreover, reversible switching between the porous structures and the close-packed structure is induced by changing the bias polarity. We identify that for this phenomenon to occur the negatively polarised O atoms of the carboxylic groups of CTA play an important role, enabling the CTA molecules at the interface to desorb and re-adsorb which is essential for switching from one ordered arrangement to the other. Our findings demonstrate that reversible switching can be controlled by manipulating the solution concentration as well as the applied bias voltage, which holds promise for controlling switchable molecular systems at the solid-liquid interface.